Leadership Superiority in Increasing the Competitiveness of Educational Institutions: Case Study at SMA N 3 Jambi City - Athiatul Haqqi; Maisah; Lukman Hakim (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2024)
This research focuses on factors that constitute strengths, weaknesses, opportunities, and threats in the context of leadership at SMA N 3 Jambi City. In educational management, there is a strategic management, which is able to identify and plan strategies, so that schools can survive and further improve their quality in the future. Therefore, this research will explore how leadership at SMA N 3 Jambi City contributes to increasing school competitiveness. Using the case study method, the research results show that leadership superiority plays a vital role in improving the competitiveness of educational institutions, including SMA N 3 Jambi City.